Scaling up tobacco cessation within TB programmes: findings from a multi-country, mixed-methods implementation study - Helen Elsey; Zunayed Al Azdi; Shophika Regmi; Sushil Baral; Razia Fatima; Fariza Fieroze; Rumana Huque; Jiban Karki; Dost Mohammad Khan; Amina Khan; Zohaib Khan; Jinshuo Li; et al. (BMC, 2022)
Abstract Background Brief behavioural support can effectively help tuberculosis (TB) patients quit smoking and improve their outcomes. In collaboration with TB programmes in Bangladesh, Nepal and Pakistan, we evaluated the implementation and scale-up of cessation support using four strategies: (1) brief tobacco cessation intervention, (2) integration of tobacco cessation within routine training, (3) inclusion of tobacco indicators in routine records and (4) embedding research within TB programmes. Methods We used mixed methods of observation, interviews, questionnaires and routine data. We aimed to understand the extent and facilitators of vertical scale-up (institutionalization) within 59 health facility learning sites in Pakistan, 18 in Nepal and 15 in Bangladesh, and horizontal scale-up (increased coverage beyond learning sites). We observed training and surveyed all 169 TB health workers who were trained, in order to measure changes in their confidence in delivering cessation support. Routine TB data from the learning sites were analysed to assess intervention delivery and use of TB forms revised to report smoking status and cessation support provided. A purposive sample of TB health workers, managers and policy-makers were interviewed (Bangladesh n = 12; Nepal n = 13; Pakistan n = 19). Costs of scale-up were estimated using activity-based cost analysis. Results Routine data indicated that health workers in learning sites asked all TB patients about tobacco use and offered them cessation support. Qualitative data showed use of intervention materials, often with adaptation and partial implementation in busy clinics. Short (1-2 hours) training integrated within existing programmes increased mean confidence in delivering cessation support by 17% (95% CI: 14-20%). A focus on health system changes (reporting, training, supervision) facilitated vertical scale-up. Dissemination of materials beyond learning sites and changes to national reporting forms and training indicated a degree of horizontal scale-up. Embedding research within TB health systems was crucial for horizontal scale-up and required the dynamic use of tactics including alliance-building, engagement in the wider policy process, use of insider researchers and a deep understanding of health system actors and processes. Conclusions System-level changes within TB programmes may facilitate routine delivery of cessation support to TB patients. These strategies are inexpensive, and with concerted efforts from TB programmes and donors, tobacco cessation can be institutionalized at scale.